Need for individualized counseling regarding psoriasis systemic therapy in women of childbearing age: analysis of the PsoFem study at the University Medical Center Hamburg - Brigitte Stephan, MD; Rachel Sommer, PhD; Matthias Augustin, MD; Nomun Ganjuur, MD; Neuza da Silva, PhD (Wolters Kluwer, 2024)
Background:. For patients with moderate-to-severe psoriasis and current childbearing/pregnancy, the choice of therapy is limited. Objectives:. The present study compared the disease burden and treatment choices in women of childbearing age (WoCBA) with and without a current wish for pregnancy. Methods:. Female patients aged 18 to 45 years, with moderate-to-severe psoriasis vulgaris, were consecutively recruited. The patients reported on sociodemographic/reproductive characteristics and quality of life impairments. The physicians assessed disease severity, comorbidities, and current treatment(s). Both patients' and dermatologists' perceptions of shared decision-making for the current systemic treatment were surveyed. Results:. Participants were 145 WoCBA with psoriasis: 73 were pregnant or reported a desire to conceive (group CB+) and 72 reported no wish to have (more) children (group CB−). Patients without childbearing wishes were older and often had previous children; no significant differences in clinical features or quality of life impairments were found. A significantly higher proportion of patients in the CB+ group were prescribed tumor necrosis factor alpha blockers, particularly certolizumab pegol. This treatment option was associated with previous children and the desire to conceive, but not with disease variables. Family planning was more often discussed and considered in the clinical decision for the CB+ group, but patient-doctor agreement for shared decision-making was fair-to-moderate. Limitations:. The small sample size prevented comparative analyses between patients planning a pregnancy in the short- vs long-term future. In addition, specific variables related to the decision-making process for the current therapy need to be assessed and examined in more detail in further research. Conclusion:. For WoCBA with childbearing wishes, tumor necrosis factor alpha blockers were most frequently prescribed, in accordance with current guidelines/recommendations. Decision-making for continuing or changing systemic therapy during pregnancy must take into account medication specificities and the vulnerable stages in pregnancy, as well as the limited amount of pregnancy-compatible drugs.